2011
DOI: 10.1128/jb.05556-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Ruegeria sp. Strain KLH11, anN-Acylhomoserine Lactone-Producing Bacterium Isolated from the Marine Sponge Mycale laxissima

Abstract: Ruegeria sp. strain KLH11, isolated from the marine sponge Mycale laxissima, produces a complex profile of N-acylhomoserine lactone quorum-sensing (QS) molecules. The genome sequence provides insights into the genetic potential of KLH11 to maintain complex QS systems, and this is the first genome report of a cultivated symbiont from a marine sponge.Sponges can harbor diverse assemblages of microbes, which in some cases can comprise up to 60% of the total biomass of the holobiont (6). This dense microbial commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
(6 reference statements)
2
15
0
Order By: Relevance
“…Annotation of the KLH11 genome revealed that KLH11 has homologues to each of the cckA , chpT and ctrA genes [11]. The putative KLH11 cckA gene (GenBank No.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Annotation of the KLH11 genome revealed that KLH11 has homologues to each of the cckA , chpT and ctrA genes [11]. The putative KLH11 cckA gene (GenBank No.…”
Section: Resultsmentioning
confidence: 99%
“…S2A). Antiserum raised against whole flagella from C. crescentus , a related alpha-proteobacterium, was able to recognize KLH11 flagellin protein encoded by the fliC gene, of approximately 41.5 kDa in size [11], [19] and was used in the western blot assay. Results showed that none of the three null mutants produced any detectable flagellin protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome sequencing of KLH11 revealed the presence of a luxI homologue, designated sscI, encoded on a large assembled sequence scaffold (.700 kb) that contains neither the ssaRI nor the ssbRI operons (Zan et al, 2011). The sscI and ssbI genes and their translation products are highly similar (70 % and 76 % nucleotide and amino acid identity, respectively) (Fig.…”
Section: Identification Of Sscimentioning
confidence: 99%